Cervical canal stenosis due to cervical spondylotic myelopathy C4-C5: A case report - Rahyussalim, Ahmad Jabir (Int J Surg Case Rep, 2019)
INTRODUCTION: Cervical spondylotic myelopathy (CSM) is a complex disease that presents with various signs and symptoms of cervical spinal cord impairment that may lead to significant clinical morbidity. PRESENTATION OF CASE: We present the case of a 50-year old man who was diagnosed with CSM. The patient underwent decompression and posterior stabilisation with open-door laminoplasty. At the 2-month follow-up, the pain subsided, function improved significantly, and weakness disappeared. The patient was also able to defecate and urinate normally. DISCUSSION: Cervical spondylotic myelopathy is a complex disease that may lead to significant clinical morbidity. The management requires an extensive knowledge of the anatomy, biomechanics, and surgical options. The variable clinical findings, radiological evidence and scoring system, such as JOA, are important for preoperative evaluation and individualising surgical planning. The choice of the most appropriate technique is affected by patient's clinical condition and radiologic findings as well as surgeon's experience. It is demonstrated that the Kurokawa-type laminoplasty that involves splitting the spinous processes in the midline offers the advantage of reduced bleeding as the lateral epidural venous plexus is not disturbed in comparison to that with the former Hirabayashi's expansive open-door laminoplasty. Moreover, the body symmetry is preserved; therefore, this procedure may be considered more anatomical and physiological. However, differences in the outcomes between the two approaches remain unknown. CONCLUSIONS: These findings suggest that the decompression and posterior stabilisation method may help achieve good patient outcomes.